A Nomogram to Predict Prognostic Value of Red Cell Distribution Width in Patients with Esophageal Cancer. (12th October 2015) - Chen, Gui-Ping; Huang, Ying; Yang, Xun; Feng, Ji-Feng
Abstract : Objectives . The prognostic value of inflammatory index in esophageal cancer (EC) was not established. In the present study, we initially used a nomogram to predict prognostic value of red cell distribution width (RDW) in patients with esophageal squamous cell carcinoma (ESCC). Methods . A total of 277 ESCC patients were included in this retrospective study. Kaplan-Meier method was used to calculate the cancer-specific survival (CSS). A nomogram was established to predict the prognosis for CSS. Results . The mean value of RDW was 14.5 ± 2.3%. The patients were then divided into two groups: RDW ≥ 14.5% and RDW < 14.5%. Patients with RDW < 14.5% had a significantly better 5-year CSS than patients with RDW ≥ 14.5% (43.9% versus 23.3%, P < 0.001). RDW was an independent prognostic factor in patients with ESCC ( P = 0.036). A nomogram could be more accurate for CSS. Harrell's c-index for CSS prediction was 0.68. Conclusion . RDW was a potential prognostic biomarker in patients with ESCC. The nomogram based on CSS could be used as an accurately prognostic prediction for patients with ESCC.